2017
DOI: 10.3390/toxins9010023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MicroRNA Expression Profiling Involved in MC-LR-Induced Cytotoxicity by High-Throughput Sequencing

Abstract: In recent years, microRNAs (miRNAs) in toxicology have attracted great attention. However, the underlying mechanism of miRNAs in the cytotoxicity of microcystin-LR (MC-LR) is lacking. The objective of this study is to analyze miRNA profiling in HepG2 cells after 24 h of MC-LR-exposure to affirm whether and how miRNAs were involved in the cytotoxicity of MC-LR. The results showed that totally 21 and 37 miRNAs were found to be significantly altered in the MC-LR treated cells at concentrations of 10 and 50 μM, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…[50, 51] Exposure of MC-LR was found promoted the expression of miR-149-3p, promoting miR-149-3p may be involved in MC-LR-hepatotoxicity, hepatitis and liver carcinoma. 52 …”
Section: Mir-149 In Drug Sensitivity and Resistancementioning
confidence: 99%
“…[50, 51] Exposure of MC-LR was found promoted the expression of miR-149-3p, promoting miR-149-3p may be involved in MC-LR-hepatotoxicity, hepatitis and liver carcinoma. 52 …”
Section: Mir-149 In Drug Sensitivity and Resistancementioning
confidence: 99%
“…Mechanistically, miRNAs directly bind to the 3'untranslated region (UTR) of their target mRNAs, leading to the degradation of mRNA or inhibition of translation (7). The expression of miRNA is tightly controlled in normal cells, for instance, dysregulation of several key miRNAs resulted in the disruption of cell signaling networks in human diseases, including cancer (8)(9)(10). With microarray analysis, many differentially expressed miRNAs are detected between ovarian tumors and normal tissues (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The qPCR results confirmed the above results, suggesting that these miRNAs may be involved in the hepatotoxicity of MC-LR. Ma et al confirmed that 21 and 37 miRNAs were altered in HepG2 cells after MC-LR exposure (10 and 50 µM) [35]. Yang reported that treatment of the HL7702 cell line with MC-LR (1, 2.5, 5, or 10 µM) clearly altered the expression of 3, 10, 9, and 99 miRNAs, respectively, when compared with control cells [34].…”
Section: Discussionmentioning
confidence: 90%
“…MCs are known to be widespread in freshwater where cyanobacteria bloom, and they are highly toxic to aquatic organisms and even humans [33]. Biological and pathological processes are assumed to be due to exposure to MC-LR and associated changes in miRNA expression levels, including metabolism, developmental timing, signal transduction, cell proliferation, differentiation, apoptosis, cancer progression, and tumorigenesis [34,35]. Meanwhile, miRNAs have been proven to regulate multiple molecular functions and have been correlated with various diseases [36,37].…”
Section: Discussionmentioning
confidence: 99%